Quantitative variations in texture analysis features dependent on MRI scanning parameters: A phantom model. (27th October 2018) - Buch, Karen; Kuno, Hirofumi; Qureshi, Muhammad M.; Li, Baojun; Sakai, Osamu
Abstract: Objectives: To evaluate the influence of MRI scanning parameters on texture analysis features. Methods: Publicly available data from the Reference Image Database to Evaluate Therapy Response (RIDER) project sponsored by The Cancer Imaging Archive included MRIs on a phantom comprised of 18 25‐mm doped, gel‐filled tubes, and 1 20‐mm tube containing 0.25 mM Gd‐DTPA (EuroSpinII Test Object5, Diagnostic Sonar, Ltd, West Lothian, Scotland). MRIs performed on a 1.5 T GE HD, 1.5 T Siemens Espree (VB13), or 3.0 T GE HD with TwinSpeed gradients with an eight‐channel head coil included T1WIs with multiple flip angles (flip‐angle = 2, 5, 10, 15, 20, 25, 30), TR/TE = 4.09–5.47/0.90–1.35 ms, NEX = 1 and DCE with 30° flip‐angle, TR/TE=4.09–5.47/0.90–1.35, and NEX = 1, 4. DICOM data were imported into an in‐house developed texture analysis program which extracted 41‐texture features including histogram, gray‐level co‐occurrence matrix (GLCM), and gray‐level run‐length (GLRL). Two‐tailed t tests, corrected for multiple comparisons ( Q values) were calculated to compare changes in texture features with variations in MRI scanning parameters (magnet strength, flip‐angle, number of excitations (NEX), scanner platform). Results: Significant differences were seen in histogram features (mean, median, standard deviation, range) with variations in NEX ( Q  = 0.003–0.045) and scanner platform ( Q  < 0.0001), GLCM features (entropy, contrast, energy, and homogeneity) with NEX ( Q  = 0.001–0.018) and scanner platform ( Q  < 0.0001), GLRL features (long‐run emphasis, high gray‐level run emphasis, high gray‐level emphasis) with magnet strength ( Q  = 0.0003), NEX ( Q  = 0.003–0.022) and scanner platform ( Q  < 0.0001). Conclusion: Significant differences were seen in many texture features with variations in MRI acquisition emphasizing the need for standardized MRI technique.